2015
DOI: 10.1021/cm503439r
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Mediated Polymorphism in Molecular Crystals: The Impact on Crystal Packing and Charge Transport

Abstract: We report a novel synthesis to ultra high purity 7,14-bis­((trimethylsilyl)­ethynyl)­dibenzo­[b,def]-chrysene (TMS-DBC) and the use of this material in the growth of single crystals by solution and vapor deposition techniques. We observe that the substrate temperature has a dramatic impact on the crystal growth, producing two distinct polymorphs of TMS-DBC; low temperature (LT) fine red needles and high temperature (HT) large yellow platelets. Single crystal X-ray crystallography confirms packing structures wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
83
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 53 publications
1
83
0
Order By: Relevance
“…Since we used the same type of metal (gold) to contact both polymorphs in the present study, contact choice alone did not cause the differences we observed. A possible reason for the unbalanced electrical properties of the two crystalline structures may be related to their different responses to the presence of the trap states and defects, as we have demonstrated for another system [48] . A more significant contribution to these differences was suggested by a recent theoretical study, which showed that the effect of molecular overlap on electronic coupling in CTs is not necessarily mirrored for holes and electrons – i.e, their transfer integrals and therefore their mobilities, do not increase and decrease simultaneously [6] .…”
Section: Discussionmentioning
confidence: 96%
“…Since we used the same type of metal (gold) to contact both polymorphs in the present study, contact choice alone did not cause the differences we observed. A possible reason for the unbalanced electrical properties of the two crystalline structures may be related to their different responses to the presence of the trap states and defects, as we have demonstrated for another system [48] . A more significant contribution to these differences was suggested by a recent theoretical study, which showed that the effect of molecular overlap on electronic coupling in CTs is not necessarily mirrored for holes and electrons – i.e, their transfer integrals and therefore their mobilities, do not increase and decrease simultaneously [6] .…”
Section: Discussionmentioning
confidence: 96%
“…7j,9d,11 Studies on acene-like structures reveal that decreasing the aromaticity within a ring system or the inclusion of antiaromatic rings into materials could greatly improve their electrical conductivity and increase charge mobilities in the solid state. 4e,5b,6,12 Recently, indenofluorenes, with their 6-5-6-5-6 fused ring systems and overall 4n π electrons, have received particular interest as indeno[1,2- b ]fluorene ( 1 ) derivatives show ambipolar charge transport in both single-crystal and thin-film OFETs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The influence of polymorphism in commercial materials is not limited to pharmaceutical applications and has been observed to affect the hydraulic properties of cement, 9 the reactivity of energetic materials, 10-13 the weather resistance of dyes, 14 the transparency of optical photonics materials 15,16 and the charge carrier mobility in semi-conductor materials. [17][18][19][20][21] Computer-based models can, in principle, rapidly and inexpensively take a particular molecule as input and search through possible crystal structures, identifying the set of stable or metastable polymorphs which are likely to be observed experimentally.…”
Section: Introductionmentioning
confidence: 99%